Digital transformation of banking: Assessing mobile banking adoption in Nepal - Lama, Padam Bahadur; Subedi, Rita Subedi; Lamichhane, Basu Dev; Karki, Murari; Chalise, Sabina (International Journal of Business Strategy and Social Sciences, 2024)
The purpose of study was to investigate the influence of perceived usefulness, perceived security, and perceived cost on behavioral intention to adopt mobile banking, which reflects the evidences from among the users of digital mobile banking services in Kathmandu, Nepal. The study fills a gap in the literature by examining the influencing factors for mobile banking adoption. This study adopted descriptive and casual correlational research design to test the hypotheses. The survey employed cross-sectional data using convenience-sampling technique, disseminated 607-structured questionnaire among the target respondents of Kathmandu municipality, Nepal, and received only 400 (65.89 percent) useful questionnaires. This study assessed the internal consistency with the value of Cronbach’s alpha where the value of Cronbach’s alpha for all constructs remained > 0.70 depicting the reliability for the analysis. Further, this study adopted descriptive statistics: frequency and percentage for the result of general information of respondents and correlation and regression analysis for testing association and impact in the study. The findings of the study showed that perceived usefulness and perceived security found positive association with behavioral intention to adopt mobile banking services, in Kathmandu, Nepal. Further, perceived cost found negative impact on behavioral intention for adoption of mobile banking services indicating inverse link between cost and mobile banking adoption. Thus, banking professionals may use this model to develop safe, practical, and easy-to-use mobile banking services to win trust of users and to boost mobile banking services. Similarly, the findings of the study extends benchmark to academics, policymakers, and others.